The Downward Spiral - Jeremy Greenwood; Nezih Guner; Karen A. Kopecky (Institute of Labor Economics (IZA), 2022)
There have been more than 500,000 opioid overdose deaths since 2000. To analyze the opioid epidemic, a model is constructed where individuals choose whether to use opioids recreationally, knowing the probabilities of addiction and dying. These odds are functions of recreational opioid usage. Markov chains are estimated from the US data for the college and non-college educated that summarize the transitions into and out of opioid addiction as well as to a deadly overdose. The structural model is constructed to match the estimated Markov chains. The epidemic's drivers and the impact of medical interventions are examined.
Keywords: D11; D12; E13; I12; I14; I31; J11; J17; 330; addiction; college/non-college educated; deaths; fentanyl; Markov chain; medical interventions; opioids; OxyContin; pain; prices; state-contingent preferences; structural model; subjective and objective beliefs